Competitive Advantage Strategies for Aluminum Store in Phetchaburi Province - Thonghnoo, Chutima (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
Competitive advantage creating was a mission that extremely important to business operations. The researcher was, therefore, interested in studying Competitive Advantage Strategies for Aluminum Store In Phetchaburi Province aiming to: 1) Study the problems of operations and marketing of Aluminum Store In Phetchaburi Province 2) creating competitive advantage strategies for Aluminum Store In Phetchaburi Province, and 3) evaluate competitive advantage strategies for Aluminum Store In Phetchaburi Province. The quantitative research samples were 15 entrepreneur, and 391 customers by multistage stage sampling. The research tools were a questionnaire with the 0.92 level of reliability. The data were analyzed by using percentage, mean, standard deviation, and Exploratory Factor Analysis with Principal component analysis (PC) and Orthogonal rotation by quartimax method. The research results were as follows: 1. The problems of operations and marketing of Aluminum Store were to ; product problems, payment methods, store arrangement, had restrictions on parking places, size of the store was not enough, acceptance from customers, lack of learning and experience in business administration, personnel problems. The original style shop that started to decline to customers used fewer services and high competition from new stores and complete construction material shop businesses. Some aluminum products had high production costs, customers do not understand the product details, delays in delivery, and employees do not recommend new products. 2. Competitive advantage strategies for Aluminum Store In Phetchaburi Province got all 10 elements, 40 variables had a range of eigen value between 7.010 - 1.306 and 59.234 percent of the variance, to inclusive; 1) Marketing strategy 2) Delivery and procurement strategy 3) Customer service strategy 4) Store and public relations strategy 5) Customer response strategy 6) Technology strategy 7) Innovation strategy 8) Marketing promotion strategy 9) Customer relationship strategy 10) Price and product standard strategy 3. Competitive advantage strategies for Aluminum Store evaluation were suitable for every strategy. Research results can be used as a guideline for Competitive advantage strategies for Aluminum Store In Phetchaburi Province By comparing the research strategy and applying it in the context of the store. Article history : Received 28 August 2019 Revised 19 November 2019 Accepted 21 November 2019 SIMILARITY INDEX = 0.83 %